Lukisan Wakidi Dalam Semiotika - Kemalasari, Rita (Institut Seni Indoensia Surakarta, 2011)
Nature unfold as a teacher maybe this minang proverb is a guidance for a wakidi in creating paintings with a naturalist genre his loving of minagkabau nature led him to remain faithful to paint the beauty of nature till the rest of his life, and in he is being well known as the mooi indie personage. Even though wakidi is not from west sumatera, but as a founding father of tradition, social behavior, and kinship system that belongs to the societies. No wonder there is a lot of researchers who want to explore and critize because his artwork has so much meaning and marks contained threin. By using various approchment as in this writing which is a combination between trichotomy icon, index, symbol and cannotative semiotics. keywords:nature, wakidi painting, semiotic.